Entrepreneurial Knowledge, Motivation, Desires, and Intention: A Content Analysis Approach - Muhammad Dharma Tuah Putra Nasution; Yossie Rossanty; Ramadhan Harahap; Aulia Ramadhan Tanjung (UNIB Press, 2024)
Entrepreneurial marketing is widely recognized for its dynamic nature, characterized by innovation and adaptability in navigating intricate market dynamics. However, a significant gap persists in understanding how entrepreneurial knowledge intersects with market dynamics. This study aims to bridge this gap by exploring the influence of entrepreneurial knowledge on motivation, desires, and intentions. It emphasizes the pivotal role of entrepreneurial knowledge in shaping market outcomes, offering valuable insights for scholars and practitioners alike. Utilizing content analysis as a fundamental research method, the study delves into qualitative data to uncover themes, words, and concepts in entrepreneurship research domains. Through this methodological approach, it meticulously tracks antecedents, mechanisms, impacts, patterns, and trends in entrepreneurship, thus enriching the understanding of entrepreneurial dynamics. Moreover, the study explores the relationship between entrepreneurial knowledge and motivation within the context of entrepreneurship. Drawing on extensive research on entrepreneurial motivation and psychological mechanisms, it elucidates how entrepreneurial knowledge serves as a primary driver of motivation, influencing attitudes, intentions, and actions toward entrepreneurial pursuits. By integrating insights from diverse perspectives, this study contributes to a deeper comprehension of the interplay between knowledge and motivation in shaping entrepreneurial behaviors. Ultimately, the findings underscore the critical importance of fostering entrepreneurial knowledge and addressing socio-cultural influences to promote entrepreneurship across diverse contexts.